Analisis Hasil Evaluasi Penyelenggaraan Bimtek Pascapanen dan Pengolahan Hasil Hortikultura di Kabupaten Panajam Paser Utara - Dewi, Christina Shanti (Seminar Nasional Lahan Suboptimal, 2024)
Dewi, C. S. (2024). Analysis of the evaluation results of post-harvest and horticultural product processing technical training in Panajam Paser Utara Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembangg 21 Oktober 2024. (pp. 573–579). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Technical guidance is carried out in order to increase the utilization of post-harvest facilities and infrastructure and product processing assistance that has been provided to farmer groups so that they can create superior products, increase the added value of products and ultimately increase the income of farmers or horticultural business actors in Penajam Paser Utara district. For this reason, an evaluation needs to be carried out to assess the success of the implementation of the technical guidance. The aimed of this research was to analyze the evaluation of the level of participant satisfaction with the trainer and the implementation and to analyze the increase in participants' knowledge and skills after following technical guidance. The method in this research uses quantitative descriptive analysis methods with a Likert scale. Based on the results of this research, it can be concluded that the participants rated the trainer very well (86.56%) and were very satisfied with the technical guidance organizers (84.84%) and there was an increase in the knowledge or skills of the participants before (1.38) in the less mastery category. and after following technical guidance (3.37) in the mastery category. It is hoped that the results of this research can be used as evaluation material and recommendations for the East Kalimantan Province Department of Food Crops and Horticulture to improve the quality of providing post-harvest technical guidance and processing of horticultural products in the following years.